Developmental Speaking as A Strategy to Enhance Communication Skills – A Cognitive Based Approach - Sreena, S.; Ilankumaran, M. (International Journal of Engineering and Technology, 2018)
Language is a particular system of communication used by human beings. It consists of development, acquisition, maintenance and use of complex systems of communication. Learning a language is not only a matter of motivation, ability and background but also it depends on the social and linguistic environment of the learners. Human beings are separated to other species in the name of communication skills. Listening skills made the people understand what another person speaks. Speaking skills are helpful to convey the wishes and idea of one person to the other in the correct way. Reading skill is essential to interpret what is given in the text. Writing is to deliver one’s thoughts. Learning strategies and processes are the most effective when they are in line with the learning style preferences. So, it becomes useful to know which learning strategy is effective to help the learners acquire the knowledge quickly and effectively. Developmental speaking is the effective strategy to enhance the communicative skills based on the process of human brain. Communication skills are necessary for a person to develop the personality. Second language is the non-native language used by the people in a locality for the communication purpose. Second language can be acquired at any age with the strategy of developmental speaking. Cognitive approach is related to the psychological factors of an individual. The paper attempts to discuss a psychological approach to enhance communication skills using developmental speaking as a strategy.